Perlindungan Terhadap Anak Sebagai Korban Kekerasan Seksual Di Wilayah Hukum Polres Bangkalan - Kharisma . (JOURNAL OF SHARIA ECONOMICS, 2022)
Sexual violence against children in Indonesia is like the tip of the iceberg. The number of cases of sexual violence against children could be much higher, but many victims lack the courage to report it to child protection agencies or the authorities. Violence occurs not only in large cities with widespread and free social interaction, but also anywhere, such as schools. Sexual violence also occurs frequently in rural areas, one of which is Bangkalan Regency. This is what motivated the author to discuss this issue. The objectives are: 1. To determine the legal protection provided to child victims of sexual violence within the jurisdiction of the Bangkalan Police. 2. To determine the obstacles faced in providing legal protection to child victims of sexual violence. The results of this study indicate that legal protection for child victims of sexual violence, based on Law No. 23 of 2002, which was amended by Law No. 35 of 2014, aims to guarantee children's rights to live, grow, and be protected from violence. The state, society, and families are obliged to provide assistance, rehabilitation, and protection of children's identities in a humane and just manner. Despite its strong legal basis, its implementation is hampered by a lack of resources, social stigma, and patriarchal culture. Law enforcement needs to be aligned with societal values to ensure the protection of children's rights as the nation's future generation.